El final de ETA: ¿lucha contra el terrorismo o resolución de conflicto? - García, Javier Ignacio (UNISCI Discussion Papers, 2007)
This article analyses the nature and dynamics of the new peace process started between the terrorist group ETA and the Spanish Government headed by President Rodríguez Zapatero. A new attempt to stop ETA’s activities, characterised by a “lack of definition”, tries to make compatible two essentially confronted approaches: a vision from the perspective of the fight against terrorism, and a vision of the process as a conflict resolution situation. To undertake a peace process with ETA on the basis of conflict resolution, trying at the same time to keep an antiterrorist policy, is conceptually incompatible. Furthermore, the Spanish Government’s inability to accept all the implications and consequences of a peace process developed under conflict resolution rules and procedures — respecting the present Spanish Rule of Law— makes this strategy non-viable